Between and within field variability of New Zealand indigenous flower visitors to onions - Howlett, B.G.; Donovan, B.J.; McCallum, J.A.; Newstrom, L.E.; Teulon, D.A.J. (New Zealand Plant Protection, 2005)
In New Zealand few studies have documented the occurrence of indigenous flower visitors within crops A fiveyear survey is examining the distribution diversity and abundance of flower visitors in onion (Allium cepa) fields located throughout New Zealand Daytime observations from the first year of the survey recorded nine arthropod orders visiting onion flowers in the South Island with Diptera (flies) and Hymenoptera being the most abundant Over six fields the proportion of bees that were indigenous species (Apoidea) ranged from lt;1 to 636 Common bee genera and fly families varied considerably in their presence and abundance even over 17 km Moreover counts of Lasioglossum spp at five points within one field ranged from 0 to 576 demonstrating that the distribution of some flower visitors can be highly variable Understanding crop flower visitors may help develop systems to reduce transgene flow should genetically modified crops be commercially produced in New Zealand